Perbandingan Penegakan Hukum Terhadap Tindak Pidana Korupsi di Indonesia dan Malaysia - Tasya Darosyifa; Handar Subhandi Bakhtiar (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Corruption remains a serious issue that hinders development and erodes public trust in the government, particularly in countries like Indonesia and Malaysia. Both nations have long histories of dealing with systemic corruption. This study aims to compare the legal systems and anti-corruption law enforcement in Indonesia and Malaysia to identify challenges and areas for improvement. The research uses a descriptive qualitative method with a Systematic Literature Review (SLR) approach, analyzing legal documents, academic journals, and regulations related to anti-corruption agencies in both countries. This study employs legal system theory and institutional theory. The main problem examined is how anti-corruption law enforcement differs between Indonesia and Malaysia and what the main enforcement challenges are. The findings show that while Indonesia’s Corruption Eradication Commission (KPK) was once powerful, recent political interference and regulatory revisions have weakened its impact. Conversely, Malaysia has more comprehensive legal instruments, but its enforcement agencies struggle with independence and political pressure. In conclusion, both countries must strengthen legal supremacy, institutional independence, and public engagement to enhance the effectiveness of anti-corruption efforts.